Construction and Evaluation of cDNA Libraries for Large-Scale Expressed Sequence Tag Sequencing in Wheat (Triticum aestivum L.) - Zhang, D. (2004)
A total of 37 original cDNA libraries and 9 derivative libraries enriched for rare sequences were produced from Chinese Spring wheat (Triticum aestivum L.), five other hexaploid wheat genotypes (Cheyenne, Brevor, TAM W101, BH1146, Butte 86), tetraploid durum wheat (T. turgidum L.), diploid wheat (T. monococcum L.), and two other diploid members of the grass tribe Triticeae (Aegilops speltoides Tausch and Secale cereale L.). The emphasis in the choice of plant materials for library construction was reproductive development subjected to environmental factors that ultimately affect grain quality and yield, but roots and other tissues were also included. Partial cDNA expressed sequence tags (ESTs) were examined by various measures to assess the quality of these libraries. All ESTs were processed to remove cloning system sequences and contaminants and then assembled using CAP3. Following these processing steps, this assembly yielded 101,107 sequences derived from 89,043 clones, which defined 16,740 contigs and 33,213 singletons, a total of 49,953 “unigenes.” Analysis of the distribution of these unigenes among the libraries led to the conclusion that the enrichment methods were effective in reducing the most abundant unigenes and to the observation that the most diverse libraries were from tissues exposed to environmental stresses including heat, drought, salinity, or low temperature.